The role of some monetary and financial policy indicators in developing gross domestic product growth: An analytical and measurement study in Iraq - Al-Sultan, Mohammed Medloal Ali; Alkarawy, Heyder G Wannes; Abdulridha, Mohammed Mohaisen (Edelweiss Applied Science and Technology, 2024)
We aim to show the basic features of monetary variables and the nature of the work of monetary policy instruments, and to try to keep pace with the changes that accompanied the action of this policy for the period between 2000–2022. We find that economic stagnation negatively affects economic growth, with increasing bottlenecks affecting the economy in the short term in Iraq. However, elucidating the fundamental characteristics of monetary variables and functioning of monetary policy indicators, such as the money supply, exchange rate, and interest rate, remains a complex task. We used the standard and analytical approach for the results established for monetary policy, the general framework, and analysis of tools, gross domestic product, economic growth, and the impact of monetary policy on economic activity in Iraq for the highest, medium, and low. Through the research, results, the independent variables have a positive effect on the dependent variable that is, increasing the gross domestic product (GDP) for a previous period by one-unit leads to an increase in the gross domestic product (GDP). According to these data, the study presented the necessity of working with monetary policy in Iraq in a way that increases the growth of the gross domestic product. Therefore, it is necessary for monetary policy to work to control the monetary mass by achieving a balanced proportion between the monetary mass and the gross domestic product in order to reach balance between real and cash.